Management of Financing for Supporting Operational Costs in the Administration of Education at SMK Hasyim Asy’ari Tegalombo - Inganatul Khasanah (Journal of Management Specialists, 2024)
This study aims to analyze and evaluate the management of financing for supporting operational costs in the administration of education at SMK Hasyim Asy'ari Tegalombo. Effective and efficient financial management is crucial to ensuring the continuity and quality of the educational process in schools. This research employs a qualitative approach with data collection techniques including interviews, observations, and documentation. The research participants consist of the school principal, treasurer, and administrative staff directly involved in school financial management. The results indicate that the management of supporting operational costs in the administration of education at SMK Hasyim Asy'ari implements School Based Management (SBM), which allows for autonomy in planning, managing, and supervising programs tailored to the school's needs. The use of funds is focused on enhancing educational services without any intervention or deductions from external parties. This management involves teachers and the school committee, adhering to the guidelines for preparing the School Budget Plan, professional fund management, and annual evaluations. The financing components at SMK Hasyim Asy'ari cover various aspects such as learning and extracurricular activities, improving the quality of educators and educational staff, participation in competitions, learning evaluations, provision of tools and learning media, maintenance of facilities and infrastructure, additional income for non-permanent teachers and staff, school literacy activities, procurement of multimedia tools, character education reinforcement, and funding for activities not covered by regular school operational assistance funds. The final evaluation of Operational Support Costs for Providing Education implementation is conducted by the SMK Hasyim Asy'ari institution, involving the entire academic community of the school, including the general treasurer, assistant treasurer, and the principal as the policy decision-maker. With effective management, BPOPP can optimize the management of supporting operational costs and improve the quality of educational services at SMK Hasyim Asy'ari Tegalombo.